The RNA polymerase activity of SARS-coronavirus nsp12 is primer dependent. - te Velthuis, A; Arnold, J; Cameron, C; van den Worm, S; Snijder, E (2010)
An RNA-dependent RNA polymerase (RdRp) is the central catalytic subunit of the RNA-synthesizing machinery of all positive-strand RNA viruses. Usually, RdRp domains are readily identifiable by comparative sequence analysis, but biochemical confirmation and characterization can be hampered by intrinsic protein properties and technical complications. It is presumed that replication and transcription of the approximately 30-kb severe acute respiratory syndrome (SARS) coronavirus (SARS-CoV) RNA genome are catalyzed by an RdRp domain in the C-terminal part of nonstructural protein 12 (nsp12), one of 16 replicase subunits. However, thus far full-length nsp12 has proven refractory to expression in bacterial systems, which has hindered both the biochemical characterization of coronavirus RNA synthesis and RdRp-targeted antiviral drug design. Here, we describe a combined strategy involving bacterial expression of an nsp12 fusion protein and its in vivo cleavage to generate and purify stable SARS-CoV nsp12 (106 kDa) with a natural N-terminus and C-terminal hexahistidine tag. This recombinant protein possesses robust in vitro RdRp activity, as well as a significant DNA-dependent activity that may facilitate future inhibitor studies. The SARS-CoV nsp12 is primer dependent on both homo- and heteropolymeric templates, supporting the likeliness of a close enzymatic collaboration with the intriguing RNA primase activity that was recently proposed for coronavirus nsp8.